Hubungan Penguasaan Kata Ulang Dengan Kemampuan Menulis Narasi Pada Siswa Kelas VII SMP Negeri 9 Tambusai Utara - Muhammad Solihin (Jurnal Sinar Edukasi, 2020)
The purpose of this study is to see whether there is a significant relationship between the mastery of the words with the ability to write narration in Class VII students of SMP Negeri 9 Tambusai Utara. The research method used by the author in this research is descriptive method. The population of this study were all Grade VII students of SMP Negeri 9 Tambusai Utara with a total of 233 students. The sample of this study was taken using cluster sampling techniques, namely VII-2 classes, amounting to 40 students. The data collection technique used is to give a test. Data analysis techniques used are descriptive analysis techniques and statistical analysis techniques. From the results of the descriptive analysis, it can be seen that the mastery of the retrospect is 66.87 which belongs to the suficient category. Meanwhile, the ability to write narration is in the good category with a value of 72.75. Then the results of the statistical analysis showed that there was a significant relationship between the mastery of words with the ability to write narratives in Class VII students of SMP Negeri 9 Tambusai Utara. This can be seen from the results of hypothesis testing, namely the value of rxy is greater than the value of r table or 0.975 > 0.320. In other words, the better the mastery of words in Class VII students of SMP Negeri 9 Tambusai Utara, the better the ability to write narration in Class VII students of SMP Negeri 9 Tambusai Utara.